EKSISTENSI AYAT-AYAT MUTASYABIHAT DALAM CAKRAWALA MUFASSIRIN - Sulkifli; Hikmawati (PAPPASANG, 2019)
The objective of this research is to disclose mufasirs’ tought of mutasyabihat verses in the holy Qur’an.This research is qualitative research which applied exegesis, linguistical, and historical approach. All the data related to some mufasirs’s thought and their view of mutasyabihat existence in Qur’an collected and processed through the approaches that given above. Data analysis technique applied as literature study used content analyses. The result of this research reveals that: (1) Mutasya>biha>t verses are verses which unclear or obscure pointing. The haziness of verse is caused by some matters, such as text, meaning, and also text and meaning all at once. (2) All mufasirs admitted the existence of mutasya>biha>t verses in the Qur’an, but different in human ability to comprehend mutasya>biha>t verses. (3) Mufassirs classify mutasyabihaat verses to be three classes; mutasyabihat verses which are not uderstanded by all human, mutasyabihat verses that human can understand the meaning by reserch, and mutasyabihat verses which can be identified by certain muslim scholar who pure their soul.